A Dynamic Model Of Sustainable Value Creation: The Impact Of Strategic Human Empowerment, Eco-Innovation, Corporate Responsibility Excellence, And Organizational Resilience On Competitive Agility And Financial Growth In The Consumer Goods Sector - Suwandi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
This study aims to analyze the impact of Corporate Responsibility Excellence, Eco-Innovation, Organizational Resilience, and Strategic Human Empowerment on Competitive Agility and Financial Growth. Using a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method, this research examines the relationships between these variables in organizations implementing sustainability and innovation strategies. The findings indicate that Competitive Agility is significantly influenced by Corporate Responsibility Excellence, Eco-Innovation, Organizational Resilience, and Strategic Human Empowerment. Meanwhile, Financial Growth is only significantly affected by Eco-Innovation and Organizational Resilience, while Corporate Responsibility Excellence and Strategic Human Empowerment do not show a significant impact on financial growth. These findings suggest that organizational competitiveness can be enhanced through sustainable innovation, organizational resilience, and strategic human resource empowerment. However, to achieve financial growth, companies should focus more on ecological innovation and strengthening business resilience. The managerial implications of this study emphasize the importance of a holistic strategy that integrates sustainability, innovation, and organizational resilience to achieve competitive advantage and sustainable financial growth.